View of CSMT from BMC - Ghosh, Ayan (Jio Institute, 2023)
Frederick W. Stevens died in 1900. During his professional career as an architect, Stevens was exceptionally prolific. Many iconic buildings in Bombay are his masterpieces. This includes, in addition to the CSMT and the BMC building, the Royal Alfred Sailor's Home (Maharashtra Police Headquarters), the Bombay, Baroda & Central India Railway Offices (Western Railway Headquarter), the Chartered Bank building, the Mulji Jetha Fountain and the Army and Navy Cooperative Society Store.